Rabies epidemiology in Malaysia (2015–2023): a cross-sectional insights and strategies for control - Wada, Yunusa Adamu; Mazlan, Mazlina; Noordin, Mohamed Mustapha; Mohd Lila, Mohd Azmi; Fong, Lau Seng; Ramanoon, Siti Zubaidah; Uda Zahli, Nurul Izzati (Elsevier, 2024)
Background: Malaysia currently faces significant challenges in controlling the spread of dog-mediated human rabies, as evidenced by recurrent outbreaks in newly affected areas and increasing human fatalities. Materials and methods: A cross-sectional study was conducted to analyse surveillance data from 2015 to 2023 to examine the epidemiological characteristics of rabies in Malaysia. Data from multiple sources were used, and descriptive statistics, incidence rates, and reproductive numbers were calculated. QGIS software was used to map the distribution of rabies cases, and statistical methods were employed to evaluate associations between rabies incidence, vaccination coverage, and risk factors. We further explored the effectiveness of vaccination campaigns and public health interventions in reducing rabies transmission. Results: Our findings revealed 995 confirmed rabies cases in animals. Sarawak reported the highest proportion of rabies cases at 97.99 %, showing a significant correlation between location and rabies cases (p < .001). Dogs comprised 89.35 % of confirmed cases, while the average annual vaccination rate was only 16.66 %, far below the 59.05 % needed for herd immunity. Moreover, human rabies cases reported in Sarawak had an alarmingly high fatality rate of 90.28 %, highlighting the urgent need for improved public health measures and surveillance. Conclusion: This research provides critical insights for policymakers and health officials to improve rabies control strategies in Malaysia.